2014
DOI: 10.7567/jjap.53.09pa04
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effect of heat treatment conditions on metalorganic-chemical-vapor-deposited ferroelectric Hf0.5Zr0.5O2thin film on Ir electrode

Abstract: The exclusive b → + − decay is analysed in the model III version of the two Higgs doublet model. We especially studied the branching ratio and the forward-backward asymmetry of this process and investigated the sensitivity of these physical observables to the model parameters. We have found that they are highly sensitive to new physics and hence provide powerful probe of the SM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 31 publications
0
58
0
Order By: Relevance
“…Seo et al reported that the rutile TiO 2 phase could hinder the m-phase formation of HfO 2 and support the t-phase formation due to the small lattice mismatch between them (rutile-TiO 2 and t-phase HfO 2 ). [56,57] TiN top electrode layer induced a tensile stress effect on the HZO film, which was why PMA samples usually showed more enhanced ferroelectric behavior than PDA samples. [55] Retardation of the m-phase growth may not be solely attributed to the rutile TiO 2 formation, but the experimental results evidently show that the m-phase formation decreased once rutile TiO 2 phase had formed.…”
Section: Resultsmentioning
confidence: 99%
“…Seo et al reported that the rutile TiO 2 phase could hinder the m-phase formation of HfO 2 and support the t-phase formation due to the small lattice mismatch between them (rutile-TiO 2 and t-phase HfO 2 ). [56,57] TiN top electrode layer induced a tensile stress effect on the HZO film, which was why PMA samples usually showed more enhanced ferroelectric behavior than PDA samples. [55] Retardation of the m-phase growth may not be solely attributed to the rutile TiO 2 formation, but the experimental results evidently show that the m-phase formation decreased once rutile TiO 2 phase had formed.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the commonly used TiN, various capping layer materials have been studied, such as Pt, 51 RuO2, 52 TaN, 40 and Ir/IrO x . 53,54 In particular, using Ir/ IrO x as electrodes has successfully solved the long-standing fatigue issue of PZT 55 and is therefore of great interest to be applied to HfO 2 -based devices. However, in the case of Si: HfO 2 thin films, the Ir capped capacitor exhibited 13-14% lower P r than the TiN capped capacitor, which was attributed to different thermal expansion coefficients and the potential scavenging effect of TiN.…”
Section: Origins Of Ferroelectricity In Hfo 2 -Based Materialsmentioning
confidence: 99%
“…24 In their reports, the magnitude of the shift depended on the annealing temperature and time. 24 On the other hand, the P-E loop shifts in the authors' previous reports were in the range of B0.05-0.2 MV cm À1 into the positive bias direction. [10][11][12]14,15 These reports showed that the sign and magnitude of E int can be varied by various factors, including electrode materials, detailed deposition process, and annealing conditions for the ferroelectric films.…”
Section: Introductionmentioning
confidence: 97%
“…21 The films can be deposited using various deposition techniques, e.g. atomic layer deposition (ALD), [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]22 RF magnetron sputtering, 23 chemical vapor deposition (CVD), 24 and chemical solution deposition (CSD). 25 Among these techniques, the ALD is considered to be ideal for depositing the conformal and uniform films on nano-structured templates because of their characteristic self-saturating mechanism.…”
Section: Introductionmentioning
confidence: 99%